Analisis Distribusi Keterlambatan Kereta Angkutan Lebaran Tahun 2016 Pada DAOP 7 - Aghastya, Adya; Adi, Wahyu Tamtomo (Politeknik Perkeretaapian Indonesia Madiun, 2017)
This research aims to analyze delays at railway train service, especially at DAOP 7 Madiun. Primary data collection is done through observation and distribution of questionnaires. Observations were made to find out the actual departure time of train departure from the station compared to the time of departure plan. The survey results show that passengers can tolerate train delays below 10 Minutes, and most (73%) can not tolerate delays longer than 10 minutes. Statistical descriptive results indicate that 49 percent of travel experiences more than 10 minutes delay, and delays vary between each train, the average delay is 16.29 minutes with a standard deviation of 27.59 minutes. Results of delays data compared in various statistical distributions show the differences of each train delay distribution, dominated by logistics distribution and Weilbul, data of the curves show density curves tend to have skewness from standard normal distributions. The overall data of the delay is most closely related to Weilbul's distribution, although it can not be concluded with 95 percent confidence that the data is distributed Weilbul. Further analysis by examining each train at the starting station to the final station is required to complete this delayed distribution review.